2011
DOI: 10.4103/0976-237x.83075
|View full text |Cite
|
Sign up to set email alerts
|

Bridge flap technique as a single-step solution to mucogingival problems: A case series

Abstract: Shallow vestibule, gingival recession, inadequate width of attached gingiva (AG) and aberrant frenum pull are an array of mucogingival problems for which several independent and effective surgical solutions are reported in the literature. This case series reports the effectiveness of the bridge flap technique as a single-step surgical entity for increasing the depth of the vestibule, root coverage, increasing the width of the AG and solving the problem of abnormal frenum pull. Eight patients with 18 teeth alto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Periodontal dressing was given to prevent epithelial re-attachment and to avoid the post-operative pain. Similar observations were also noted by Gupta et al 7 This new innovative surgical approach will definitely help in gaining not only sufficient sulcus depth, but also esthetically pleasant appearance. It also demonstrated that this procedure in children offers predictable success, when conditions are suitable and are correctly selected.…”
Section: Discussionsupporting
confidence: 85%
“…Periodontal dressing was given to prevent epithelial re-attachment and to avoid the post-operative pain. Similar observations were also noted by Gupta et al 7 This new innovative surgical approach will definitely help in gaining not only sufficient sulcus depth, but also esthetically pleasant appearance. It also demonstrated that this procedure in children offers predictable success, when conditions are suitable and are correctly selected.…”
Section: Discussionsupporting
confidence: 85%
“…Of the 16 articles focusing only on Miller class III GRs, nine of them [ 7 , 31 , 35 , 38 , 39 , 57 , 61 , 62 , 64 ] treated single GRs, six studies [ 6 , 53 , 56 , 58 60 ] included multiple GRs, and one study [ 67 ] included single or multiple Miller class III GRs. In the rest of articles, different kind of GRs were treated: single Miller class I, II and III GRs were treated in nine studies [ 40 , 41 , 44 , 48 , 50 , 51 , 63 , 65 , 66 ], whereas multiple Miller class I, II, III and IV GRs were treated in five articles [ 45 , 46 , 52 , 54 , 68 ], and single and multiple Miller class I, II and III GRs were treated in other seven articles [ 14 , 42 , 43 , 46 , 47 , 49 , 55 ] (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the treatment of Miller class III [ 4 ] or RT2 [ 5 ] recessions, the tunnel preparation and the CAFs were the most widely used surgical techniques. Regarding surgical procedures developed along twentieth century, they were used in 16 clinical studies [ 7 , 14 , 43 , 44 , 47 49 , 51 , 53 , 57 , 59 , 61 , 62 , 65 – 67 ] (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical parameters included Probing Pocket Depth (distance from gingival margin to base of pocket), Gingival Recession (distance from cemento-enamel junction to gingival margin), width of attached gingiva (distance from base of pocket to mucogingival junction), and Clinical Attachment Level (distance from cemento-enamel junction to base of pocket). [6] The procedure was well explained to the patient and informed consent was obtained for surgery. The patient was medically sound and fit, so a surgical procedure was planned.…”
Section: Case Reportsmentioning
confidence: 99%